Nia ta kdak / Me and the Other - Philippe Charland (Recherches amérindiennes au Québec, 2017)
This article is a discussion of the ethnonyms used by the Abenaki people to designate other indigenous nations with which they had contact. As with many toponyms, these ethnonyms have been subject to variations throughout history that make reading, understanding and interpreting them difficult; these variations arise mainly from a lack of knowledge of native languages and the bureaucratisation of their vocabulary. Through exhaustive research of the ethnonyms available in primary sources, it was possible to identify 19 ethnonyms referring to 14 Indigenous groups of the northeast (Algonquin, Attikamek, Huron-Wendat, Inuit, Iroquois, Maliseet, Micmac, Passamaquoddy, Mohawk, Mohican, Naskapi, Nipissing, Odawa and Penobscot). Several of the ethnoynms identified were found to be loanwords from other Algonquian languages, while some groups were designated by more than one ethnonym. Also of note is the fact that for certain indigenous groups of Quebec, no Abenaki-language ethnonym could be identified in spite of documented contact between the two groups. Cet article traite des ethnonymes employés par les Abénakis, à travers le temps, pour désigner les nations autochtones les côtoyant. Comme bien des toponymes, les ethnonymes ont subi différentes variations à travers le temps, variations dues entre autres à la méconnaissance des langues autochtones et à la bureaucratisation de ce vocabulaire, qui rendent de nos jours difficiles leur lecture, leur compréhension et leur interprétation. À travers une recherche exhaustive des ethnonymes disponibles dans les sources primaires, il a été possible d’identifier dix-neuf ethnonymes se rapportant à quatorze groupes autochtones du Nord-Est (Algonquin, Attikamek, Huron-Wendat, Inuit, Iroquois, Malécite, Micmac, Passamaquoddy, Mohawk, Mohican, Naskapi, Nipissing, Odawa et Pénobscot). Plusieurs des ethnonymes trouvés se sont avérés être des emprunts linguistiques à d’autres langues algonquiennes, et certains groupes sont identifiés par plus d’un ethnonyme. Assez étrangement, certains ...